An evaluation of the monetary transmission mechanisms in South Africa - Thlaku, Thabang (School of Economics, 2015)
The aim of this paper is to see whether the adoption of the Inflation Targeting regime has had an impact on the Monetary Transmission Mechanisms in South Africa. I employ a reduced-form VAR model to test the strength of the Monetary Transmission Mechanisms during two distinctly different monetary policy regimes. I investigate the strength of the various transmission channels during the Monetary Targeting regime using data from 1986-1999 and the Inflation Targeting regime using data from 2000-2010.